The Social Reality of Korean Pop Culture Enthusiasts Among Teenagers in Bandar Lampung: A Case Study of Moments of Alwaysness (MOA) Community - Simarmata, Enjel Karlelita; Hernawan , Wawan; Pienrasmi, Hanindyalaila (Interaction Communication Studies Journal, 2025)
This study aims to explore the social reality of teenagers who are fans of Korean popular culture, particularly those involved in the Moments of Alwaysness (MOA) fandom community in Bandar Lampung. Using a qualitative approach and a case study method, the research focuses on how communication practices, group dynamics, and identity construction emerge within this fandom. The study employs five theoretical frameworks: social reality theory, representation theory, social identity theory, interpersonal communication theory, and group communication theory. Data were collected through in-depth interviews, participant observation, and documentation of social media interactions. The findings reveal that teenagers use K‑Pop fandom not only as a space for entertainment but also as a medium for identity exploration, social bonding, and self-expression, both online and offline. The community serves as a cultural and social platform where members internalize values, norms, and collective meanings, shaping a shared reality within the local context. This study contributes to a deeper understanding of youth behavior in the digital era and highlights how global popular culture influences local social dynamics among adolescents.